2020
DOI: 10.5761/atcs.ra.19-00158
|View full text |Cite
|
Sign up to set email alerts
|

Current Management of Acute Pulmonary Embolism

Abstract: Purpose: Acute pulmonary embolism (PE) remains a significant cause of morbidity and requires prompt diagnosis and management. While non-surgical approaches have supplanted surgery as primary treatment, surgical pulmonary embolectomy (SPE) remains a vital option for select patients. We review the current management of acute PE, with a focus on surgical therapy. Methods: A PubMed search was performed to identify literature regarding PE and treatment. Results were filtered to include the most comprehensive public… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
76
0
15

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(92 citation statements)
references
References 40 publications
1
76
0
15
Order By: Relevance
“…d. Dobutamine in medium doses of up to 10 μg/kg/min can be considered as inotrope of choice. However, it should be kept in mind that, dobutamine administrated at improper high doses, increases perfusion of nonventilated regions of the lungs and may worsen respiratory insufficiency secondary to increased ventilation-perfusion (V/P) mismatch [5][6][7].…”
Section: Oxygen and Ventilatory Supportmentioning
confidence: 99%
See 2 more Smart Citations
“…d. Dobutamine in medium doses of up to 10 μg/kg/min can be considered as inotrope of choice. However, it should be kept in mind that, dobutamine administrated at improper high doses, increases perfusion of nonventilated regions of the lungs and may worsen respiratory insufficiency secondary to increased ventilation-perfusion (V/P) mismatch [5][6][7].…”
Section: Oxygen and Ventilatory Supportmentioning
confidence: 99%
“…f. Based on minimal clinical data it may be suggested that if CO remains low despite vasopressors and inotropes, a pulmonary vasodilator trial with iNO may be beneficial when pulmonary hypertension is present [5][6][7][8].…”
Section: Oxygen and Ventilatory Supportmentioning
confidence: 99%
See 1 more Smart Citation
“…Acute pulmonary embolism (APE) 2 is one of the typical and most dangerous illnesses with a 30-day average death rate of ~10%. 1 The existence of right ventricular (RV) disorder is correlated to a considerable rise in hospitalization and mortality due to pulmonary embolism (PE). 1,2 Prior research shows that an inflammatory response is a crucial factor in the dysfunction of the right ventricle after APE.…”
Section: Introductionmentioning
confidence: 99%
“…Pulmonary embolism (PE) is the third-leading cause of cardiovascular-related death in the United States, accounting for around 100,000 deaths per year [ 1 ]. Specifically, massive (or high-risk) PE, defined as acute PE with sustained hypotension and hemodynamic instability, accounts for an estimated 4.5%-10% of all PE cases and has over 50% mortality [ 2 , 3 ]. Historically, the primary treatment options for PE have been anticoagulation therapy and systemic thrombolytic therapy.…”
Section: Introductionmentioning
confidence: 99%